Discovery and serological validation of DAMP-derived B-cell epitopes as diagnostic biomarkers for diabetic nephropathy - Yu, Chengyuan; Dong, Yishi; Zhong, Fuhua; Zeng, Jun; Fang, Zhiye (Frontiers in Endocrinology, 2025)
BackgroundDiabetic nephropathy (DN), a severe complication of diabetes and a leading cause of end-stage renal disease, is strongly associated with chronic inflammation triggered by damage-associated molecular patterns (DAMPs), such as high-mobility group box 1 (HMGB1), S100A8, and S100A9. This study aimed to identify and validate conserved B-cell epitopes from these DAMPs to develop peptide-based serological markers for DN diagnosis.MethodsCanonical sequences of HMGB1 (NP_002119.2), S100A8 (NP_002955.1), and S100A9 (NP_002956.2) were retrieved from NCBI RefSeq. Evolutionary conservation was assessed using MAFFT v7.520 and ConSurf. Linear epitopes were predicted with BepiPred 2.0 (threshold = 0.5) and ABCpred (threshold = 0.51), while conformational epitopes were mapped using ElliPro (score ≥ 0.5, distance ≤ 6Å) on crystallographic structures (PDB: 2YRQ, 1XK4). Candidate epitopes were evaluated for antigenicity (VaxiJen v2.0, threshold = 0.5), surface accessibility (DSSP > 20%), and cross-reactivity (BLASTp against UniProtKB/Swiss-Prot 2024_03). Top peptides were synthesized via Fmoc-SPPS (≥ 95% purity, confirmed by HPLC/MS) and validated using indirect enzyme-linked immunosorbent assay (ELISA) on sera from DN patients (n = 30) and healthy controls (n = 30). Diagnostic performance was assessed via receiver operating characteristic (ROC) analysis.ResultsThree highly immunogenic and evolutionarily conserved linear B-cell epitopes were identified: HMGB1 (GSSGMGKGDPKKPRGK, VaxiJen = 1.60), S100A8 (NSIIDVYHKYSLIKGN, 1.20), and S100A9 (SVKLGHPDTLNQGEFK, 0.70). These epitopes overlapped with predicted conformational regions and were confirmed to be surface-exposed through structural modeling. ELISA analysis revealed significantly elevated IgG responses in DN patient sera versus controls (p < 0.01), with the HMGB1-derived peptide showing the most robust and specific immunoreactivity, highlighting its strong diagnostic potential.ConclusionThis study successfully identified and validated three novel DAMP-derived B-cell epitopes with significant diagnostic potential for diabetic nephropathy. The peptides exhibited high immunogenicity, strong specificity, and consistent performance in ELISA-based serological assays. These findings pave the way for the development of noninvasive, peptide-based diagnostic tools for early DN detection. Future efforts will focus on multicenter validation and integration into multiplex serological panels.